2015
DOI: 10.1002/ange.201505625
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Cluster Metalation and Ligand Migration in Zirconium Metal–Organic Frameworks

Abstract: Cooperative cluster metalation and ligand migration were performed on a Zr‐MOF, leading to the isolation of unique bimetallic MOFs based on decanuclear Zr6M4 (M=Ni, Co) clusters. The M2+ reacts with the μ3‐OH and terminal H2O ligands on an 8‐connected [Zr6O4(OH)8(H2O)4] cluster to form a bimetallic [Zr6M4O8(OH)8(H2O)8] cluster. Along with the metalation of Zr6 cluster, ligand migration is observed in which a Zr–carboxylate bond dissociates to form a M–carboxylate bond. Single‐crystal to single‐crystal transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…63 Recently, it was reported that the μ 3 -OH groups of the SBUs in Zr/Hf MOFs can serve as active sites for binding metal cations. 64,65 To determine the dominating sites within NUS-6(Hf) in binding Ag(I), we prepared another Hf MOF, namely, UiO-66(Hf), with roughly the same SBUs but without any sulfonic acid groups in the framework. 66 UiO-66(Hf)-Ag was obtained by treating UiO-66(Hf) with AgBF 4 under conditions identical to those used for NUS-6(Hf)-Ag.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…63 Recently, it was reported that the μ 3 -OH groups of the SBUs in Zr/Hf MOFs can serve as active sites for binding metal cations. 64,65 To determine the dominating sites within NUS-6(Hf) in binding Ag(I), we prepared another Hf MOF, namely, UiO-66(Hf), with roughly the same SBUs but without any sulfonic acid groups in the framework. 66 UiO-66(Hf)-Ag was obtained by treating UiO-66(Hf) with AgBF 4 under conditions identical to those used for NUS-6(Hf)-Ag.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Indeed, we observed that the -OH À / H 2 Ogroups along c-direction selectively deprotonate to react with basic metal hydroxides,w hereas the -OH À /H 2 Og roups along the b-direction tend to act as bases to react with molybdic acid ( Figure S46). [14] To further support our hypothesis,weused density functional theory (DFT) to calculate the relative acidities of Zr 6 models of PCN-700-o and PCN-700-c (see Supporting Information, Section S9). Thec alculated DpK a value for the PCN-700-o-Zr 6 model (the pK a of -OH À / H 2 Oa long the b-direction minus the one along the cdirection) is 0.56.…”
Section: Angewandte Chemiementioning
confidence: 98%
“…Thehalved active site in PCN-700-c is expected to reduce the V max by half.H owever,t he experimental data suggested that the V max (PCN-700-c) is actually reduced by 84 % compared to that of V max . [14] To further support our hypothesis,weused density functional theory (DFT) to calculate the relative acidities of Zr 6 models of PCN-700-o and PCN-700-c (see Supporting Information, Section S9). Indeed, we observed that the -OH À / H 2 Ogroups along c-direction selectively deprotonate to react with basic metal hydroxides,w hereas the -OH À /H 2 Og roups along the b-direction tend to act as bases to react with molybdic acid ( Figure S46).…”
Section: Angewandte Chemiementioning
confidence: 98%